2013
DOI: 10.3846/20296991.2013.806702
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Slope From Raster Data – A Test of Eight Algorithms at Different Resolutions in Flat and Steep Terrain

Abstract: Different slope algorithms can result in totally different estimates. In the worst case, this may lead to inappropriate and useless modelling estimates. A frequent lack of awareness when choosing algorithms justifies a thorough comparison of their characteristics, making it possible for researchers to select an algorithm which is optimal for their purpose. In this study, eight frequently used slope algorithms applied to Digital Elevation Models (DEMs) are compared. The influences of the resolution of the DEM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…25 , 26 The calculation of the slope of the land was generated from a digital elevation model (DEM) that allows for the calculation of the specific slope of territory. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%
“…25 , 26 The calculation of the slope of the land was generated from a digital elevation model (DEM) that allows for the calculation of the specific slope of territory. 27 , 28 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the slope algorithms may also affect the accuracy of the CSHDSI calculation. Tang et al (2013) found statistical differences in slope results across 8 algorithms. Four scholars believe that the slope accuracy of the third-order finite difference algorithm (3FDA) is higher than that of the second-order finite difference algorithm (2FDA), while three scholars have reached the opposite conclusion (Liu et al, 2004).…”
mentioning
confidence: 87%
“…The differences of CSHDSI between using 2FDA (3FDA) and 2TPA-AHS show there are more significant negative deviations (Figures 5e-5l). Tang et al (2013) pointed out that the more points involved in the calculation for slope, the stronger the smoothing effect of the finite difference.…”
Section: The Accuracy Of 2tpa the Hpftoa 2fda And 3fdamentioning
confidence: 99%
“…Алгоритм расчета уклона и экспозиции элементарной поверхности. Из восьми существующих в настоящее время алгоритмов расчета уклона в разрабатываемой системе применяется наиболее устойчивый из них [Tang et al, 2013].…”
Section: рис 5 схема объектов элементарных поверхностей и их взаимосв...unclassified